PENINGKATKAN PRESTASI BELAJAR IPA MELALUI METODE EKSPERIMEN LEARNING - Ermida Ermida (Jurnal Bidang Pendidikan Dasar, 2019)
AbstractExperiment Method Learning in classroom learning is part of an experiment to observe an object, analyze data, prove and draw conclusions on an object and prove a particular question or hypothesis that allows students to experiment to prove themselves a question or hypothesis being studied. This research is a type of PTK class action research (Action research class) with the aim of Research to: (1) Describe the experimental method of learning in improving learning outcomes of elementary school science (2) Improve the achievement of science learning outcomes through the Learning Experiment method (3) Describe the increase in science learning activities through the Experiment learning method. The class action research design used is the Kemmis taggart cycle model. The results of this study indicate that learning model Experimental Learning learning methods have a positive impact on improving student learning achievement. The success criteria that have been determined by the researcher reached in the second cycle, namely the average percentage score of the final test results increased from 73% to 88%, this shows that students' conceptual understanding is getting better and the percentage of student activity observation increases from 80% to 92.5%, p. it shows that students are very active in the learning process in the classroom. ABSTRAKMetode Eksperiment Learning dalam pembelajaran dikelas merupakan bagian dari percobaanuntuk mengamati suatu objek, menganalisis data, membuktikan dan menarik kesimpulan sendiri tentangsuatu objek dan membuktikan suatu pertanyaan atau hipotesis tertentu yang memungkinkan siswamelakukan percobaan untuk membuktikan sendiri suatu pertanyaan atau hipotesis yang dipelajari. Penelitianini berjenis penelitian tindakan kelas PTK (Action research class) dengan tujuan Penelitian untuk:(1)Mendiskripsikan metode eksperimen learning dalam peningkatan hasil belajar IPA SD (2) Menigkatkanprestasi hasil belajar IPA melalui metode Eksperimen Learning (3) Mendiskripsikan peningkatan aktivitasbelajar IPA melalui metode Eksperiment learning. Desain penelitian tindakan kelas yang digunakan adalahmodel siklus Kemmis taggart, Hasil penelitian ini menunjukkan bahwa pembelajaran pembelajaranEksperimen Learning memiliki dampak positif dalam meningkatkan prestasi belajar siswa. Kriteriakeberhasilan yang telah ditetapkan peneliti tercapai pada siklus II yaitu persentase rata-rata skor hasil tesakhir meningkat dari 73% menjadi 88%, hal ini menunjukkan bahwa pemahaman konsep siswa semakin baikdan persentase observasi kegiatan siswa meningkat dari 80% menjadi 92.5%, hal tersebut menunjukkansiswa sangat aktif dalam proses pembelajaran di kelas